2003
DOI: 10.1002/rcm.1171
|View full text |Cite
|
Sign up to set email alerts
|

Analytical method for the quantitative determination of urinary ethylenethiourea by liquid chromatography/electrospray ionization tandem mass spectrometry

Abstract: A direct, rapid and selective method for the quantitative determination of the ethylenethiourea (ETU) in human urine has been validated and is reported in the present study. It allows the accurate quantification of ETU in this complex matrix without the use of any internal standard as the sample cleanup is effective enough for the removal of interferences that could lead to ion suppression in the electrospray ionization (ESI) source. This simple and rapid purification system, based on the use of a Fluorosil ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 21 publications
3
23
0
1
Order By: Relevance
“…This decrease could be explained by its pronounced water solubility. These results are consistent with previous studies (Kaushik et al, 2009;Timme & Walz-Tylla, 2004). It was indeed demonstrated that surface residues are amenable to simple washing operations whereas systemic residues present in tissues will only be affected to a limited extend.…”
Section: Washingsupporting
confidence: 93%
See 4 more Smart Citations
“…This decrease could be explained by its pronounced water solubility. These results are consistent with previous studies (Kaushik et al, 2009;Timme & Walz-Tylla, 2004). It was indeed demonstrated that surface residues are amenable to simple washing operations whereas systemic residues present in tissues will only be affected to a limited extend.…”
Section: Washingsupporting
confidence: 93%
“…It was indeed demonstrated that surface residues are amenable to simple washing operations whereas systemic residues present in tissues will only be affected to a limited extend. Polar, water-soluble pesticides are more readily removed than low-polarity materials (Burchat et al, 1998;Holland et al, 1994;Timme & Walz-Tylla, 2004). The effectiveness of washing in removing residues depends on the location, the water solubility of the pesticide and the temperature of the wash.…”
Section: Washingmentioning
confidence: 99%
See 3 more Smart Citations